A EDUCAÇÃO AMBIENTAL E SUA CONTRIBUIÇÃO PARA O DESENVOLVIMENTO COMUNITÁRIO: O CASO DA COOPERATIVA DOS CATADORES E AGENTES AMBIENTAIS DE IRATI (COCAAIR) - Horst, Luciane Vanessa Mendes (2015)
In this thesis I study Environmental Education as a community development strategy at the Cooperative of Collectors and Environmental Agents of Irati, Paraná (Cocaair). The community consists of 20 collectors, who are responsible for the collection, sorting and marketing of recyclable materials. Apparently, Cocaair is a cohesive and spontaneous group, with a strong relation of identity and belonging. However, it presents, as an association, several environmental, social, organizational, political and labor shortcomings. The research was based on an extensive revision on the concepts of Environmental Education, Environment and Community Development and its relation to the disposal of waste during the application of the National Solid Waste Plan. The study was based on ethnographic research with field work, carried out from the obtained experience among collectors for ninety days. The results indicated that recycling, as long as it is promoted from an environmental education work that values the emancipation of the subjects, ethics and environmental justice can contribute to the community development process at Cocaair.